DETERMINANTS OF INTENTION TO DONATE ON SHARE WAQF: THE CASE OF MUSLIM WORKERS IN JAKARTA - Nashrudin Ismail; Tatik Maryanti (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2022)
This research aims to analyze the factors influencing the intention to donate shares waqf of Indonesian Muslim employees, using an extended theory of planned behavior and adding knowledge of share waqf, trust in nazhir, and religiosity as the variables. This research is expected to enrich the literature regarding the intention to donate shares waqf and can be used to increase the collection of shares waqf in the future. This study uses a quantitative method to see the factors that affect the intention to donate shares among Muslim employees. The data obtained through online surveys of Muslim employees in Jakarta will be analyzed using SEM-PLS. The findings of this study indicate that four variables: attitude, perceived behavior control, trust, and religiosity, have no positive influence on people's intentions to donate shares waqf. While two other variables, subjective norm, and knowledge, can be proved to positively influence the intention to donate shares waqf. Because waqif characteristics and behaviors are important, this research can be used to create a more effective campaign framework for waqf, which is expected to increase people's intention to donate on share waqf. This research is expected to contribute to at least three elements of waqf: knowing factors of the intention to donate on share waqf, improving people's knowledge of share waqf, and increasing the potentiality to grow share waqf in Indonesia.